Designing an antigen Covid-19 tests evaluation ontology and knowledge graph - Haniková, Kateřina (2023)
This master thesis focuses on creating an ontology from existing XML data about antigen Covid-19 tests. The data was gathered manually from different resources regarding the sensitivity and specificity of antigen Covid-19 tests. The XML file served only for the web presentation, and the data structure was adjusted for this purpose. Since no dataset of this kind was found, it was decided to create a knowledge graph to open the data to broader reuse. To do so, an ontology was designed to give the data proper semantics. The field of ontology engineering is constantly evolving, and many tools, methods and methodologies exist for developing ontologies. It depends on an ontological engineer and a domain of interest which methods and tools will be preferred. The ontology developed in this thesis is called the Antigen Covid-19 Tests Evaluation Ontology (ACTE) and was designed from competency questions. Also, this work includes a simple analysis of the data with SPARQL queries to inspire future development. In the end, the ontology designed in OWL was reengineered with PURO Modeler.